Disposition '87 : An Introduction to Contemporary Irish Painting. - Rijkscentrum Hoger Kunstonderwijs, Brussel (Brussel : Rijkscentrum Hoger Kunstonderwijs, 1987)
Ballagh, Robert ; Behan, John ; Bourke, Brian ; Campbell, George ; Egan, Felim ; Fallon, Conor ; Farrell, Micheal ; Gale, Martin ; Hanlon, Jack ; Harper, Charles ; Harris, Pat ; Henessy, Patrick ; Hone, Evie ; Jellett, Mainie ; King, Cecil ; le Brocquy, Louis ; McGuinness, Norah ; Mulcahy, Michael ; O'Malley, Tony ; O'Neill, Daniel ; Scott, Patrick ; Tyrrell, Charles ; Warren, Michael ; Woods, Gordon
Disposition '87 : An Introduction to Contemporary Irish Painting, Rijkscentrum Hoger Kunstonderwijs, Brussel, 4-14 June 1987
boek